Design and development of a memory game solution for players with and without visual impairment - Gerding, Thiago Morano; Otsuka, Joice Lee; Fontoura Junior, Paulo H. F. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2018)
As games have risen as one of the most popular forms of entertainment, they have also been proved to be good educational resources. However, because this media often focuses on the visual aspects, people with visual impairments are often unable to make use of them. Thus, the aim of this study is to propose a design solution of a multiplatform memory game that targets people with and without visual impairments. For this, studies on design solutions for accessible memory games on different platforms are analysed. A design proposal is presented, which is based on these solutions, as well as on guidelines of accessibility and playability. Finally, a low fidelity prototype is used to test the interaction of a visually impaired player.